Music in their time : the memoirs and letters of Dora and Hubert Foss - Foss, Hubert J. (Hubert James), 1899-1953; Foss, Dora (The Boydell Press, 2019)
An intimate and readable account, filled with interesting and amusing anecdotes, of a highly creative period in English musical history.